How Light Affects Circadian Rhythm and Mood Regulation - Fu, Juan (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Light is full of the world and illuminates our lives, and scientists believe that light must play a crucial role in affecting humans either positively or negatively including circadian functions and emotion-related behaviors. Through experiments, researchers have revealed the fact that light can affect humans significantly and the principles behind phenomena of light influencing humans both physically and mentally. This essay focuses on how light works in humans’ circadian rhythm and mood regulation, and how exactly nocturnal light exposure induces depression-like behaviors. Many research results indicate that natural light can help reset circadian rhythm of humans when the normal circadian rhythm is disturbed by trans meridian travel or working during night. Thus, scientific time of light exposure helps to relieve jet-lag symptoms and allows people to have a healthier mental and physical state. Studies by Fernandez D C et al. and An K. et al. are included in this essay to demonstrate the effects of light on mood. Fernandez D C et al. experimentally confirm that PHb (perihabenular nucleus) is necessary in the circuit of light affecting mood through ipRGC which is the only receptor of light input to influence circadian functions of the brain. Subsequently, An K. et al. conducted a series of experiments on mice to investigate the role of a subcortical pathway regulated by circadian rhythms in modulating mood-related behaviors resulted from nighttime light exposure in mice. The findings provide insights into the mechanisms underlying the impact of nocturnal light on mood regulation and highlight the importance of considering circadian rhythms in understanding the effects of environmental factors on mental health. Overall, these studies allow more scientists to think about how to employ light as therapy as well as development of new anti-depressants based on the research of the ipRGC circuit.